Efficient degradation of metronidazole wastewater over MIL-101(Fe) Fenton catalysts. (20th February 2023) - Zhang, Xu; Lyu, Yang; Zhang, Jie; He, Bai; Xiong, Wei; Jiang, Songshan
Abstract : Complete degradation of high concentration metronidazole wastewater with low dosage of MIL-101(Fe) by Fenton catalysts. Abstract : The MOF Fenton catalyst (MIL-101(Fe)) was developed and used for the efficient catalytic wet peroxide oxidation (CWPO) of metronidazole (MNZ) wastewater at a low reaction temperature. MIL-101(Fe) was characterized by XRD, SEM, FT-IR spectroscopy, and XPS. The catalytic activity of MIL-101(Fe) was investigated by CWPO of metronidazole wastewater with a high concentration of 200 mg L −1 . In particular, the effects of calcination temperature (300–500 °C), degradation temperature (30–60 °C) and catalyst dosage (25–100 mg in 500 mL wastewater) on the CWPO of metronidazole wastewater were studied. The characterization results certificated the successfully synthesis of MIL-101(Fe), and the XPS analysis showed the valence state of the Fe species affected by the calcination temperature, while FT-IR results further demonstrated the structural and thermal stability of the catalyst. The MIL-101(Fe) Fenton catalysts exhibited excellent catalytic activity in the simulated MNZ wastewater, which was fast and completely degraded ( X MNZ = 100%, X H2 O2 = 83%, in 20 minutes). The MIL-101(Fe) catalysts retained high activity even at low temperatures (40 °C) and low catalyst usage (25 mg in 500 mL wastewater). The catalytic activity of MIL-101(Fe) was affected by the valence state of the Fe element, which was proved by the XPS results. The catalytic activity of Fe 3+ in MIL-101(Fe) is higher than the Fe 3+ in Fe2 O3 . MIL-101(Fe) is a potential energy-efficient Fenton catalyst for the degradation of nitroimidazole antibiotics in the environmental field.